Factors influencing brand equity of sportswear brand among Generation Y in UiTM Bandaraya Melaka / Nurul Fatihah Noorafuddin - Noorafuddin, Nurul Fatihah (Faculty of Business and Management, 2018)
This research purpose is to study the factors that influencing brand equity of sportswear brand among generation Y in UiTM Bandaraya Melaka. Since there are a lot of new brand come into the industry, brand equity become more crucial day by day. Moreover, there are varieties of factors to achieve high brand equity. In this study, four (4) factors were adopted which is brand association, brand awareness, brand loyalty and brand image. These studies were focus for the population of generation Y in UiTM Bandaraya Melaka. 150 sets of questionnaires were distributed and only 120 were returned. The results from this study found that brand image is the factor that gives the greatest impact on brand equity. Convenience sampling was the sampling method for this study. The data of correlation and regression was analysed by using SPSS.